Impact of the source and serial passaging of goat mesenchymal stem cells on osteogenic differentiation potential: implications for bone tissue engineering. Issue 1 (December 2016) - Elkhenany, Hoda; Amelse, Lisa; Caldwell, Marc; Abdelwahed, Ramadan; Dhar, Madhu
Abstract Background Adult mesenchymal stem cells (MSCs) can be conveniently sampled from bone marrow, peripheral blood, muscle, adipose and connective tissue, harvested from various species, including, rodents, dogs, cats, horses, sheep, goats and human beings. The MSCs isolated from adult tissues vary in their morphological and functional properties. These variations are further complicated when cells are expanded by passaging in culture. These differences and changes in MSCs must be considered prior to their application in the clinic or in a basic research study. Goats are commonly used as animal models for bone tissue engineering to test the potential of stem cells for bone regeneration. As a result, goat MSCs isolated from bone marrow or adipose tissue should be evaluated usingin vitro assays, prior to their application in a tissue engineering project. Results In this study, we compared the stem cell properties of MSCs isolated from goat bone marrow and adipose tissue. We used quantitative and qualitative assays with a focus on osteogenesis, including, colony forming unit, rate of cell proliferation, tri-lineage differentiation and expression profiling of key signal transduction proteins to compare MSCs from low and high passages. Primary cultures generated from each source displayed the stem cell characteristics, with variations in their osteogenic potentials. Most importantly, low passaged bone marrow MSCs displayed a significantly higher and superior osteogenic potential, and hence, will be the preferred choice for bone tissue engineering in futurein vivo experiments. In the bone marrow MSCs, this process is potentially mediated by the p38 MAPK pathway. On the other hand, osteogenic differentiation in the adipose tissue MSCs may involve the p44/42 MAPK pathway. Conclusions Based on these data, we can conclude that bone marrow and fat-derived MSCs undergo osteogenesis via two distinct signaling pathways. Even though the bone marrow MSCs are the preferred source for bone tissue engineering, the adipose tissue MSCs are an attractive alternative source and undergo osteo-differentiation differently from the bone marrow MSCs and hence, might require a cell-based enhancer/inducer to improve their osteogenic regenerative capacity.